SISTEM INFORMASI PELAYANAN PERUSAHAAN LISTRIK NEGARA (PLN) CABANG MUARA TEMBESI BERBASIS WEB: Service;Report;Web Based. - Rusli, Mulyadi; Firlana, Aji (JURNAL AKADEMIKA, 2021)
Technological developments accompanied by developments in science demand that everything be done quickly and accurately, especially at the MuaraTembesi branch of the PLN, because this agency has the duty to serve the public in the electricity sector. To improve work efficiency and effectiveness, especially in the data processing section, the MuaraTembesi Branch PLN Service Information System was created. New Customer Data Collection on a WEB-based basis. The results obtained from this study are data processing of new electricity installation customers which results in the design of information systems and new customer data collection through the PLN web which provides an overview of customer data processing using a computerized system. The purpose of this research is to produce an information system design for data collection of new customers of the State Electricity Company (PLN) at the MuaraTembesi Branch. And for its benefits, namely simplifying and accelerating performance in the registration process and customer data collection, simplifying data processing and making it easier to make reports to officers regarding applicant data reports and customer data.